Determinants of stigma among patients with hepatitis C virus infection. Issue 11 (23rd June 2020) - Saine, M. Elle; Szymczak, Julia E.; Moore, Tyler M.; Bamford, Laura P.; Barg, Frances K.; Schnittker, Jason; Holmes, John H.; Mitra, Nandita; Lo Re, Vincent
Abstract: Stigma around hepatitis C virus (HCV) infection is an important and understudied barrier to HCV treatment and elimination. The determinants of HCV‐related stigma, including the impacts of stage of HCV treatment (ie spontaneously cleared; diagnosed, untreated; previously treated, not cured; currently being treated; and treated, cured) and coinfection with human immunodeficiency virus (HIV), remain unknown. To address these gaps, we conducted a cross‐sectional study among patients with a history of HCV infection (n = 270) at outpatient clinics in Philadelphia from July 2018 to May 2019. We evaluated stigma using the validated HCV Stigma Scale, adapted from the Berger HIV Stigma Scale. Associations among HCV‐related stigma and hypothesized demographic, behavioural, and clinical risk factors were evaluated by multivariable linear regression. Most participants (95.5%) experienced HCV‐related stigma. Mean stigma scores did not differ significantly between HCV‐monoinfected and HIV/HCV‐coinfected participants ( P  = .574). However, we observed significant interactions between HIV status and multiple determinants; therefore, we stratified analyses by HIV status. Among HIV/HCV‐coinfected participants, previous HCV treatment without cure, female gender, Hispanic/Latinx ethnicity and some college education were significantly associated with higher HCV‐stigma scores. An annual income of $10 000‐$40 000 was associated with significantly lower stigma scores. No significant associations were observed among HCV‐monoinfected participants. We found that most participants experienced stigma associated with HCV diagnosis. While stigma scores were similar between HCV‐monoinfected and HIV/HCV‐coinfected participants, the determinants associated with HCV stigma differed by HIV status. Understanding how experiences of stigma differ between HCV‐monoinfected and HIV/HCV‐coinfected patients may aid in the development of targeted interventions to address the HCV epidemic.